Flawless - Graham, Heather (Graham, Heather. New York confidential, 2016)
There's a pub in New York City that's been in the Finnegan family for generations. Now Kieran and her three brothers own it. Kieran Finnegan is also, as it happens, a criminal psychologist--a fitting reaction, perhaps, to her less-than-lawful teenage past. Meanwhile, New York's Diamond District has been hit by a rash of thefts. No one's been killed - until now. FBI agent Craig Frasier is brought in to investigate; he and Kieran meet at a jewelry store in the middle of a heist. She's there to "unsteal" a flawless stone taken by her light-fingered youngest brother as an act of vengeance. Craig's there to stop the gang.